RAPID ANALISYS OF VITAMIN-C CONTENT IN ACEROLA EXTRACT BY FT–NIR SPECTROSCOPY (Revista Tecnológica, 2013)
The acerola fruit, also known as cherry-of-Antilles or cherry-of-Barbados was originated in the West Indies and belongs to the Malpighiaceae family. It has pro-vitamin A carotenoids, vitamins B1 (thiamin), B2 (riboflavin), B3 (niacin), calcium, phosphorus, iron and especially vitamin-C, which is its main nutritional appeal. In consequence of this, develop methodologies for a rapid and accurate determination of vitamin-C content in the extract of this fruit is of academic and commercial interest, since the levels of this vitamin decay in function of time. The application of FT-NIR technology for predicting the quantification of vitamin-C content in acerola extract is a new methodology that has being adapted and exploited to provide reliable results in this field. To develop this work, the vitamin-C content was originally determined by the iodide ions reduction and the results were used to calibrate the FT-NIR apparatus in order to develop a calibration curve by using PLS (Partial Least Squares) treatment. The calibration range obtained lies between 0.38 to 2.15% of vitamin-C which has an associated prediction error of 0.067%. The curve obtained proved to be enough accuracy to be routinely used in rapid analysis of the vitamin-C content in acerola extract.